Consumerism in online health information search and self‐tracking devices - Ertiö Titiana; Räsänen Pekka (Wiley, 2022)
The Internet hosts a plethora of health information and has become a popular source users turn to when looking up information. Nonetheless, the existence of this wealth of online health information generates challenges related to access and user skills. Whereas previous studies surveyed a cross‐section of users, our aim is to complement them with a population‐level study. We use nationally representative data collected by Statistics Finland between 2006 and 2016 to investigate the extent to which online health information search and use of self‐tracking devices associate with social, economic and demographic factors. We have used descriptive statistics and logistic regressions to show that, in 2016, disparities still existed in how Finns make use of the health information found online as well as appropriate new devices such as self‐tracking devices.